Pengaruh Promosi Media Sosial Terhadap Penjualan di Bukalapak - Fahmi Zain; Dedi Mulyadi (Yayasan Daarul Huda Kruengmane, 2023)
Along with economic growth and technological developments, the business world is also experiencing rapid development with the emergence of various companies that are trying to create products and services to meet the needs and desires of consumers. The widespread use of social media, for example: Facebook, Twitter and other social media communication forums, inevitably forces companies to improve their communication models. This social media device is a common thing that is always in touch with our activities, especially for internet users. Promotion is one element of the marketing mix (marketing mix), in addition to determining the selling price, product and distribution. This study aims to determine the effect of promotion through social media, and the attractiveness of the sale of Bukalapak. The population in this study are all people who use Bukalapak. The sample size is 100 respondents, the sampling technique is to distribute questionnaires to people who use Bukalapak. The type of data used comes from primary data and secondary data. Data collection was carried out using a questionnaire, the results of this study also show several indicators that Bukalapak must improve again, the analysis results also show some results that can be developed in terms of promotion at Bukalapak, such as service, attractiveness of promotions provided, information provided displayed, and the convenience of shopping at Bukalapak.